Context-sensitive reconfiguration of collaborative manufacturing systems. Issue 13 (2019) - Caesar, Birte; Nieke, Michael; Köcher, Aljosha; Hildebrandt, Constantin; Seidl, Christoph; Fay, Alexander; Schaefer, Ina
Abstract: To stay competitive in a highly dynamic environment, manufacturing companies have to quickly react to changing customer demands. Manufacturing systems may only serve demands that are covered by their capabilities. The manufacturability of a product can be analyzed by comparing the provided capabilities against the product's requirements. The manufacturing capabilities depend on the current system and subsystem configuration. If a product cannot be manufactured, first, it must be analyzed whether any valid configuration exists that provides the required capabilities, and second, the system has to be reconfigured according to the new configuration. To the best of our knowledge no existing method exists that enables these previously mentioned steps. In this paper, we introduce a method for context-sensitive reconfiguration of multiple collaborating manufacturing systems that might come from different vendors to create a customized product on demand. We utilize variability models to capture the possible configuration space and describe influences of product properties on features of the variability model by providing a context-sensitive variability model. We apply our method to a demonstrator and show that we enable modeling of reconfigurable manufacturing systems that are automatically reconfigured on context change.